Business history around the world - Amatori, Franco; Jones, Geoffrey (Comparative perspectives in business history., 2003)
This book offers the first in-depth international survey of current research and debates in business history. Historians here document and analyze the evolution of a wide range of important companies, their patterns of innovation, production, and distribution, their financial affairs, their political activities, and their social impact.